In Vitro Antimicrobial, Insecticidal, Antitumor, Antioxidant activities and their Phytochemical Estimation of Methanolic Extract and its Fractions of Nepeta praetervisa leaves - Yasser Al-kahraman; Nizam Baloch; Abdul Manan Kakar; Sajid Nabi (International Journal of Phytomedicine, 2012)
The aim of the present investigation deals with biological evaluation Nepeta praetervisa leaves. For this purpose different biological assay of methanolic extract (Crude) and its fractions that are chloroform fraction, n-hexane fraction, Ethyl acetate fraction, n-butanol fraction and aqueous fraction were carried out. The results from the agar diffusion method indicated that Crude showed maximum antibacterial activity against Staphylococcus aureus with the inhibition zone (31.18±0.01mm). On the other hand, Crude showed maximum activity against Candida albicans and Candida glaberata with % inhibition of (76.10%±0.02%) and (82.02%±0.11%) respectively. Furthermore, Crude showed maximum insecticidal % mortality against both Tribolium castaneum and Sitophilus oryzea with (80%) mortality. On the other hand, Crude also showed tremendous Antitumor activity with % inhibition 85.23% as comparable to the standard drug. Chloroform fraction showed maximum DPPH free radical scavenging activity with the IC50 value of 19.66μg/ml. Furthermore, the phytochemical estimation of Crude and its fractions showed the presence of Alkaloids, Flavonoids, Phenols, tannins and Diterpenes.